GPi-DBS may induce a hypokinetic gait disorder with freezing of gait in patients with dystonia - Schrader, Christoph; Capelle, Hans-Holger; Kinfe, Thomas M.; Blahak, Christian; Bäzner, Hansjörg; Lütjens, Götz; Dressler, Dirk; Krauss, Joachim K. (Neurology, 2011)
Objectives: Stimulation-induced hypokinetic gait disorders with freezing of gait (FOG) have been reported only recently as adverse effects of deep brain stimulation (DBS) of the globus pallidus internus (GPi) in patients with dystonia. The aim of this work was to determine the frequency and the nature of this GPi-DBS-induced phenomenon. - Methods: We retrospectively screened our database of patients with dystonia who underwent DBS. Patients with focal, segmental, or generalized dystonia of primary or tardive origin and no gait disorder due to lower limb dystonia before DBS, bilateral pallidal stimulation, and a follow-up for more than 6 months were included. Reports of adverse events were analyzed, and gait abnormalities were scored by comparing preoperative and postoperative video recordings using Movement Disorder Society-sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) items 3.10 (gait) and 3.11 (FOG). To assess the role of GPi-DBS in gait abnormalities, DBS was paused for 24 hours. Gait and FOG were assessed 30 minutes, 2 hours, and 24 hours after restarting DBS. Finally, a standardized adjustment algorithm was performed trying to eliminate the gait disorder. - Results: Of a collective of 71 patients with dystonia, 6 presented with a new gait disorder (8.5%; 2 men, 4 women, mean age 61.3 years [48-69 years], 2 craniocervical, 1 DYT-1 segmental, 1 truncal, 2 tardive dystonia). GPi-DBS improved Burke-Fahn-Marsden Dystonia Rating Scale motor score by 54% and disability score by 52%. MDS-UPDRS item 3.10 worsened from 0.5 (±0.8) to 2.0 (±0.9) and item 3.11 from 0 to 2.5 (±0.5). The gait disorder displayed shuffling steps and difficulties with gait initiation and turning. Increasing voltages improved dystonia but triggered FOG, sometimes worsening over a period of a few hours. It vanished within minutes after ceasing DBS. Electrode misplacement was ruled out. In all but one patient, no optimal configuration was found despite extensive testing of settings (monopolar, bipolar, pulse width 60-210 μs, frequency 60-180 Hz). Nevertheless, a compromise between optimal stimulation for dystonia and eliciting FOG was achieved in each case. - Conclusions: A hypokinetic gait disorder with FOG can be a complication of GPi-DBS.
Gesehen am 26.10.2022